Expression of Nerve Growth Factor, Brain-Derived Neurotrophic Factor and Neurotrophin-3 mRNAs in Human Cortical Xenografts. (1995) - Humpel, Christian; Strömberg, Ingrid; Olson, Lars
Abstract : Trophic factors play an important role in the development of neurons and glia. In order to study the involvement of neurotrophins in human cortical development, human fetal parietal cortical tissue, obtained after early elective abortions, was transplanted to cortical cavities in immunosuppressed rats. Using in situ hybridization it was demonstrated that nerve growth factor, brain-derived neurotrophic factor and neurotrophin-3 mRNAs are expressed in developing human cortical xenografts. We conclude that neurotrophins may play a role in human cortical development and rat-derived astroglial cells could be involved in establishing reciprocal "permissive sites".